2016
DOI: 10.1016/j.ijdevneu.2016.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient developmental excitatory neuronal activity fails to foster establishment of normal levels of inhibitory neuronal activity

Abstract: The nervous system is composed of excitatory and inhibitory neurons. One major class of inhibitory neurons release the neurotransmitter γ-Aminobutyric acid (GABA). GABAergic inhibitory activity maintains the balance that is disrupted in conditions such as epilepsy. At least some GABAergic neurons are initially excitatory and undergo a developmental conversion to convert to inhibitory neurons. The mechanism(s) behind this conversion are thought to include a critical developmental increase in excitatory activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…This is underscored by studies with ex vivo neuronal networks. Our studies and those of other laboratories demonstrate that ex vivo neuronal networks can model multiple aspects of the nervous system, including development [42], maturation [36], longterm potentiation [43], environmental interaction [43,57], aging [31] and ultimate neurodegeneration [72 -75]. While the "default" interpretation of neuronal behavior is perhaps to consider stimulation as evoking response, our studies underscore the additional requirement of inhibitory neuronal activity for the achievement of both the development as well as maintenance of complex "responsive" actions of the nervous system.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…This is underscored by studies with ex vivo neuronal networks. Our studies and those of other laboratories demonstrate that ex vivo neuronal networks can model multiple aspects of the nervous system, including development [42], maturation [36], longterm potentiation [43], environmental interaction [43,57], aging [31] and ultimate neurodegeneration [72 -75]. While the "default" interpretation of neuronal behavior is perhaps to consider stimulation as evoking response, our studies underscore the additional requirement of inhibitory neuronal activity for the achievement of both the development as well as maintenance of complex "responsive" actions of the nervous system.…”
Section: Discussionsupporting
confidence: 62%
“…This transient excitatory activity of GABAergic neurons also contributed to the level of total excitatory signaling required to trigger the developmental conversion of initially excitatory GABAergic neurons to inhibitory neurons [42]. Moreover, insufficient GABAergic excitatory activity actually inhibited this developmental transition.…”
Section: The Role Of Inhibitory Neurons In the Development Maturatiomentioning
confidence: 96%
See 1 more Smart Citation
“…These analyses may contribute to optimization of neuronal-computer interfaces for perceptive and locomotive prosthetic applications. Manipulation of inhibitory neuronal activity and initial connectivity may provide insight into perturbations of balance in excitatory/inhibitory activity that promote seizures and/or perturb motor activity in epilepsy and Parkinson’s disease [ 4 - 6 , 29 ]. In addition, the inherent potentially-interfering basal activity of an amplitude matching sensory input in our system may provide a useful system for analyses of conditions such as attention deficit hyperactivity disorder, where competing sensory and internal distractions can distract an individual from task recognition and completion.…”
Section: Discussionmentioning
confidence: 99%
“…C. elegans possesses an ortholog of FUS, known as FUST-1, sharing approximately 50% identity at the protein level. Previous studies reported that deletions in fust-1 led to neuronal degeneration and paralysis, while overexpression did not exhibit any discernible effects [ 57 ]. Studies in C. elegans have unveiled structural and functional similarities between FUS and TDP-43, showing comparable outcomes when mutated ALS-associated variants are expressed [ 48 ].…”
Section: Molecular Mechanisms Of Als In C Elegans ...mentioning
confidence: 99%